Penggunaan Strategi Struktural dan Semantik Dalam Terjemahan Cerita Rakyat Jepang “Donguri dan Kucing Hutan” Karya Antonius Pudjo - Febi Ariani Saragih (Unipdu Jombang, 2017)
AbstractIn the world of translation, translators can use a variety of strategies. One is the structural and semantic strategy. This research discusses the method of translation by using the structural and semantic strategy of Japanese folk literature translated by Antonius Pudjo. There are three basic strategies related to structural issues, namely addition, subtraction, and transposition. As for the semantic strategy there are 9 strategies: levy, cultural equivalent, descriptive equivalent and component analysis, synonym, official translation, depreciation and expansion, addition, deletion, and modulation. This research is qualitative descriptive research. Research data is the translation of the story